Pembelajaran Tutor Teman Sebaya Menggunakan Bantuan LKPD untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik - Kurnia Fermani Hidayah (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
Learning activities are very important in providing learning experiences that enable students to build their own knowledge. However, based on observations, it is known that the learning outcomes for class XII IPA-1 and This research aims to improve students' activities and learning outcomes by using the peer tutoring method and assisted by LKPD. This research is qualitative research in the form of Classroom Action Research (PTK) which was carried out in 2 cycles. Based on the research results, it was found that students' learning activities had increased compared to before. This can be seen from the results obtained, for class XII IPA-1 with high activity criteria of 56% and very high 22%. Meanwhile, for class XII IPA-4, the criteria are high, 54%, and very high, 31%. Student learning outcomes have also increased. Students who have reached the minimum KKM for class XII IPA-1 are 78% and for class XII IPA-4 it is 85%.